Relationship between Emotional Intelligence, Sleep Quality and Body Mass Index in Emergency Nurses - Miguez-Torres, Noelia (Healthcare (Basel), 2021)
Nurses have long working hours with high psychological burdens. In addition, in the emergency department, nurses are required to quickly adapt emotionally. The aim of this study was to describe and relate emotional intelligence (EI) skills of emergency nurses, their body mass index (BMI) and sleep quality. For this purpose, a cross-sectional was carried out in which the perceived emotional intelligence test and the Pittsburgh sleep quality index were applied. Sixty-two emergency nurses (48 women and 14 men) participated. The results indicated that the majority of them present adequate levels of EI, with no differences by gender. Younger nurses showed a better ability to feel, express and understand emotional states than the older ones, while the ability to regulate emotional states occurred in the opposite way. Nurses who have been working for several years showed a better ability to regulate emotions than those with less experience. Those who were overweight grade II and obese type I expressed their feelings better, also the regulation of emotional states decreased as weight increased. Finally, it has been observed that the quality of sleep of emergency nurses is significantly altered, and that this lack of sleep may affect their ability to process emotions.